Belgium : Technical Note on Securities Markets Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2013)
The Belgian securities market and financial services markets have remained subdued since the crisis, and significant changes have taken place in regulatory architecture in response. The execution requires both the resources and the same strong focus on driving key outcomes. Concerns also remain about the risk of regulatory arbitrage arising from differences in regulatory and supervisory approaches between the National Bank of Belgium (NBB) and the Financial Services and Markets Authority (FSMA). Efforts to solidify cooperation and integration of work between the NBB and the FSMA should continue along with investor education work.